Mission Foundations and other Essays : Biblical and Missiological Studies from Malawi - Nkhoma, Jonathan Samuel (Book collections on Project MUSE., 2020)
The first two essays in this book examine the biblical and philosophical basis for mission in the post-modern world, emphasizing the experiential quality of mission over against the rational. Subsequent essays discuss various aspects of mission with a focus on the Malawian context. They highlight the impact of missionary work on the formation, shaping and developments of Malawi as a national state. Other essays examine various issues in New Testament scholarship including images of the Historical Jesus and how these relate to wisdom and apocalyptic traditions.